A comparative analysis of dispersal syndromes in terrestrial and semi‐terrestrial animals. (10th June 2014) - Stevens, Virginie M.; Whitmee, Sarah; Le Galliard, Jean‐François; Clobert, Jean; Böhning‐Gaese, Katrin; Bonte, Dries; Brändle, Martin; Matthias Dehling, D.; Hof, Christian; Trochet, Audrey; Baguette, Michel; Chase, Jonathan
Abstract Dispersal, the behaviour ensuring gene flow, tends to covary with a number of morphological, ecological and behavioural traits. While species‐specific dispersal behaviours are the product of each species' unique evolutionary history, there may be distinct interspecific patterns of covariation between dispersal and other traits ('dispersal syndromes') due to their shared evolutionary history or shared environments. Using dispersal, phylogeny and trait data for 15 terrestrial and semi‐terrestrial animal Orders (> 700 species), we tested for the existence and consistency of dispersal syndromes across species. At this taxonomic scale, dispersal increased linearly with body size in omnivores, but decreased above a critical length in herbivores and carnivores. Species life history and ecology significantly influenced patterns of covariation, with higher phylogenetic signal of dispersal in aerial dispersers compared with ground dwellers and stronger evidence for dispersal syndromes in aerial dispersers and ectotherms, compared with ground dwellers and endotherms. Our results highlight the complex role of dispersal in the evolution of species life‐history strategies: good dispersal ability was consistently associated with high fecundity and survival, and in aerial dispersers it was associated with early maturation. We discuss the consequences of these findings for species evolution and range shifts in response to future climate change.